Information needs and information-seeking behavior of employees at the Armed Forces and Police Savings and Loan Association, Inc. (AFPSLAI) a user study - Gaerlan, Aldric Rodolfo Z. II; Pascua-Cruz, Ma. Divina A. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2004)
This study was done in order to determine the information need and information-seeking behavior of employees of the main branch of The Armed Forces & Police Savings & Loan Association, Inc. (AFPSLAI), a private Non-Stock Savings and Loan Association(NSSLA) whose clientele is limited to a "well-defined market" from the Armed Forces of the Philippines (AFP), Philippine National Police (PNP) and selected sub-agencies of the Department of Interior and Local Government (DILG), such as the Bureau of Fire Prevention (BFP) and Bureau of Jail Management and Penology (BJMP), and to give a picture of the information system being used and improvements to be made if necessary.
Data was gathered by the conduction of a survey using questionnaires; with the sample population determined using the stratified random sampling method. Using the survey, it was determined that the population was predominantly female, within the ages of 31-36, employed for 6-10 years and rank-and-file employees. Information needs for employees were predominantly about policies and procedures in order to keep abreast with current changes in the former for both rank-in-file and managers alike. Most of the employees felt that the existing information system satisfied their information needs. Those that did not cited updated membership information for employees and compiled & complete company policies & procedures, and readily available external data (political/economic updates, competitors' data, etc.) for easy reference for managers and supervisors as information gaps. Most rank-and-file employees utilized reference materials in seeking information. Managers and supervisors mostly attended seminars, conferences and meetings for the same purpose. In the location and awareness of needed information, the primary tools for the job used by employees were company manuals and memorandum circulars. The most common institutional barrier faced by employees in the satisfaction of information needs was the lack of technical resources. In terms of personal barriers encountered by employees, lack of facilities rated primary for rank-in-file and lack of technical resources for managers & supervisors. Due to the existence of these barriers, the following recommendations were reached: conduct a system analysis study of the existing system and an analysis of previous studies, upgrading of facilities found inadequate in the fulfillment of employee information needs, and an increase in resources used in the availability of information.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Armed Forces and Police Savings and Loan Association, Inc. (AFPSLAI).; Employees -- Attitudes; Information service -- Use studies